2012
DOI: 10.1038/nature11283
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in APP protects against Alzheimer’s disease and age-related cognitive decline

Abstract: The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
1,307
1
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,520 publications
(1,355 citation statements)
references
References 24 publications
38
1,307
1
9
Order By: Relevance
“…4 A more recent study reported a variant of the APP gene (APPA673T) at a site proximal to the BACE1 proteolytic site that confers protection against AD. 5 A673T substitution in APP results in reduced production of Aβ peptides secreted from heterologously transfected cells, further supporting the hypothesis that increases in Aβ may underlie the pathology of AD. Cleavage of APP by β-site APP cleaving enzyme-1 (BACE1) results in shedding of the APP ectodomain, and the remaining membrane bound C-terminal fragment, C99, is further processed by γ-secretase to produce Aβ.…”
supporting
confidence: 59%
“…4 A more recent study reported a variant of the APP gene (APPA673T) at a site proximal to the BACE1 proteolytic site that confers protection against AD. 5 A673T substitution in APP results in reduced production of Aβ peptides secreted from heterologously transfected cells, further supporting the hypothesis that increases in Aβ may underlie the pathology of AD. Cleavage of APP by β-site APP cleaving enzyme-1 (BACE1) results in shedding of the APP ectodomain, and the remaining membrane bound C-terminal fragment, C99, is further processed by γ-secretase to produce Aβ.…”
supporting
confidence: 59%
“…According to the prevailing amyloid‐cascade hypothesis, A β deposition in the brain triggers the hyperphosphorylation of tau and its accumulation as neurofibrillary tangles, activation of inflammatory cells and pathways, initiation of oxidative stress, and decline in synaptic and neuronal health and finally neurodegeneration 8. This view recently gained further support from the identification of a protective APP variant (A673T), which was later shown to reduce A β levels and protect against cognitive decline 9, 10. Physiologic functions of A β are not well‐established, but significant lines of evidence suggest that A β may have potential protective properties under certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Support for the amyloid cascade hypothesis was spurred by the identification of mutations in amyloid precursor protein (APP) that are associated with familial AD [6][7][8] or protection against amyloid pathology and age-related Alzheimer's disease. [9][10][11] In addition, it was discovered that overexpression of APP due to trisomy 21 in Downs disease was associated with a high incidence of AD in these individuals. [12][13][14] Today it is clear that the pathological tau also plays a vital role in the development of AD pathology and progression of this disease, 15 correlating better with the degree of dementia than Ab plaques.…”
Section: Introductionmentioning
confidence: 99%